2015
DOI: 10.1002/app.42463
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐pegylated chitin whiskers as an effective additive to enhance the mechanical properties of recycled ABS

Abstract: The recyclability of materials is a key issue related to the use of polymers in the automotive and electronic industries, among others. The multiple thermal and mechanical operations used in recycling can cause severe damage to the molecular architecture and microstructure of polymers that frequently leads to a reduction in their mechanical properties, which restricts their recyclability. In this work, nanocomponents (whiskers) derived from chitin were surface‐modified by grafting different molar masses of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…The peak of the loss modulus [Figure (b)], corresponding to the glass transition temperature ( T g ) of the styrene–acrylonitrile (SAN) component of ABS, shifted toward lower temperatures when L‐CNC was added to ABS. This behavior indicated that L‐CNC may have interpenetrated regions of ABS rich in SAN, forming a miscible blend at the interface and reducing the T g of the SAN phase . Comparing the T g of nanocomposites with different L‐CNC contents, it was found that the T g of the 4% composite was higher than that of the others, indicating better interaction between L‐CNC and ABS was obtained when 4% L‐CNC was added as shown by the morphology of the fractured nanocomposites in Figure .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The peak of the loss modulus [Figure (b)], corresponding to the glass transition temperature ( T g ) of the styrene–acrylonitrile (SAN) component of ABS, shifted toward lower temperatures when L‐CNC was added to ABS. This behavior indicated that L‐CNC may have interpenetrated regions of ABS rich in SAN, forming a miscible blend at the interface and reducing the T g of the SAN phase . Comparing the T g of nanocomposites with different L‐CNC contents, it was found that the T g of the 4% composite was higher than that of the others, indicating better interaction between L‐CNC and ABS was obtained when 4% L‐CNC was added as shown by the morphology of the fractured nanocomposites in Figure .…”
Section: Resultssupporting
confidence: 81%
“…This behavior indicated that L-CNC may have interpenetrated regions of ABS rich in SAN, forming a miscible blend at the interface and reducing the T g of the SAN phase. 39 Comparing the T g of nanocomposites with different L-CNC contents, it was found that the T g of the 4% composite was higher than that of the others, indicating better interaction between L-CNC and ABS was obtained when 4% L-CNC was added as shown by the morphology of the fractured nanocomposites in Figure 5.…”
Section: Resultsmentioning
confidence: 95%